2003
DOI: 10.1136/ard.62.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparative study of patients with culture proven and high suspicion of adult onset septic arthritis

Abstract: Objective: To investigate whether patients with acute septic arthritis (SA) diagnosed by positive synovial fluid (SF) culture (Newman grade A) have different clinical and serological features from those with sterile SF in whom there is nonetheless a high suspicion of SA (Newman grades B and C). Patients and methods: A prospective 12 month multicentre hospital based study of adult patients with SA recruited 47 patients with culture positive SA and 35 patients with clinically suspected SA but sterile SF. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
3
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 25 publications
5
85
3
8
Order By: Relevance
“…In our patient population less than half of the patients with septic ankle arthritis had an elevated WBC on admission. The elevation of nonspecific markers of inflammation such as ESR and CRP has been associated with septic arthritis [2,4,5]. Our data support these notions, because every patient in our study had an elevated ESR and CRP levels on admission.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In our patient population less than half of the patients with septic ankle arthritis had an elevated WBC on admission. The elevation of nonspecific markers of inflammation such as ESR and CRP has been associated with septic arthritis [2,4,5]. Our data support these notions, because every patient in our study had an elevated ESR and CRP levels on admission.…”
Section: Discussionsupporting
confidence: 80%
“…Our data support these notions, because every patient in our study had an elevated ESR and CRP levels on admission. Staphylococci and streptococci are the most common causative organisms of septic arthritis [1,2,4,5]. In 2000, Lee et al [8] reported, among a cohort of 29 adults and children diagnosed with septic ankles, S. aureus was the most common offending organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above findings raise the spectre of a group of patients with suspected septic arthritis but culture-negative synovial fluid. Gupta et al in their prospective study comparing patients with culturenegative septic arthritis to patients with culture-proven septic arthritis found that the demographics, clinical examination, laboratory parameters, complications rates and the use of supportive measures were similar in the two groups [17].…”
Section: Discussionmentioning
confidence: 99%
“…A similar frequency (22 of 104, 21%) was shown in a recent study, and the presence of microcrystals did not exclude SA. 13 Finally, the opinion of the clinician who has the basic biological results possibly even the macroscopic appearance of the synovial fluid but not the result of its analysis, is relevant but not consistent; SA was not the most probable diagnosis in 5/38 (13%) of the SA cases. This could be explained by an over-reliance on the diagnostic value of fever and elevated inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%